تحليل الأخطاء الكتابية عند طلبة قسم تعليم اللغة العربية في الجامعات الإسلامية الأهلية بأتشية - Nyak Mustakim (Sekolah Tinggi Ilmu Tarbiyah Al-Hilal Sigli Aceh- Indonesia, 2020)
The purpose of this study is to analyze the foams of writing errorsin the students of arabic langguage education at PTKIS Aceh and to uncover the cauces of wtiting errors. This study used a qualitative descriptive approach, and the data collection with analysis of documentation and interview with the lecture, source data is written documentation of students arabic langguage at PTKIS Aceh and teachers of arabic. The results of this study show that the types of writing errors by student of arabic langguage education at PTKIS Aceh consists of the addition, subtraction errors and mistakes a sentence, that errors includes by sentence idhofah, sentence na'at, sentence of jumlah ismiyah, the use of dhomair, the sentence of jumlahfi'liyah, use a'dat, use of fi'il nawashik and huruf nawashik, errors of sentencefi'il mutaddi and use harf jar.The cauces of wtiting errors is cauced by learning methode, lack of pratice, intralingual tranfer (less of syntax understanding).